1986
DOI: 10.1007/bf02907312
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of LHCII genes in mesophyll and bundle sheath cells of maize

Abstract: The properties and composition of bundle sheath and mesophyl! thylakoids from maize leaves are compared. This was possible because of the isolation of large amounts of purified material obtained by enzymatic digestion of mechanically disrupted leaves. Bundle sheath thylakoids from mature leaves, lack the chlorophyll-proteins and polypeptides associated with the reaction centre ofphotosystem II. They do, however, contain significant amounts of LHCII, which transfers excitation energy to photosystem I. LHCII iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 14 publications
4
22
0
Order By: Relevance
“…1) represent artifacts caused by detergent solubilization, as reported previously (53,54). A relatively high ratio of LHCII/PSII in maize bundle sheath chloroplasts (14,56) and the significant increase of the functional antenna of PSI within these membranes prompted suggestions that LHCII may act as the antenna for PSI in this compartment (19,57,58). We therefore examined whether a fraction of LHCII may transiently associate with the LHCI⅐PSI supercomplex, leading to an observed increase of the PSI absorption cross-section (data not shown).…”
Section: Discussionmentioning
confidence: 81%
“…1) represent artifacts caused by detergent solubilization, as reported previously (53,54). A relatively high ratio of LHCII/PSII in maize bundle sheath chloroplasts (14,56) and the significant increase of the functional antenna of PSI within these membranes prompted suggestions that LHCII may act as the antenna for PSI in this compartment (19,57,58). We therefore examined whether a fraction of LHCII may transiently associate with the LHCI⅐PSI supercomplex, leading to an observed increase of the PSI absorption cross-section (data not shown).…”
Section: Discussionmentioning
confidence: 81%
“…LHCII has been shown to be composed of at least five polypeptides in maize (5). Proteolytic digestion studies indicated that LHCII is an extremely stable complex held together by noncovalent interactions -presumably hydrogen bonding between charged or polar residues buried in the membrane -even when the polypeptide chain was cleaved in so many places that the peptides were too small to be detected after electrophoresis under denaturing condi-lions on polyacrylamide gels containing 6 Murea.…”
Section: Discussionmentioning
confidence: 99%
“…The light-harvesting complex of photosystem II (LHCII) in maize is composed of at least five polypeptides with slightly different mobilities during SDS-PAGE (5). Analyses of the nuclear genome in tomato and petunia have shown that the genes coding for polypeptide components of LHCII are present in several copies and organized in five small multigene families (12,26).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, BS thylakoids mostly carry out cyclic electron flow and have low rates of linear electron flow (9 -11). After several conflicting reports on protein levels of PSII and light-harvesting complex (LHC) II (11)(12)(13), a subsequent study partially clarified both activity and protein accumulation levels of PSI and PSII complexes in BS and M thylakoids (14). However, a more comprehensive overview of accumulation levels and assembly state of the thylakoidbound photosynthetic apparatus remains to be determined.…”
mentioning
confidence: 99%